(untitled) (Altre Modernità, 2015)
The magazine “SSSR na stroike” (“USSR in Construction”) published in Russia, Germany, France, England was born in the early 1930s from an idea of Maksim Gorky. It was conceived as the successor of another well-known issue, “Nashi dostizhenia” to let the whole Europe know about the progress and successes of the First Five-Year Plan and of the related Soviet system. Beyond the propaganda, “SSSR na stroike” had another main task: opposing the negative image the Russians émigrés gave of their native country abroad. Official portraitists by the Soviet élite, photographers, intellectuals and artists with whose works USSR celebrated and created their own myths were chosen to realize this project. That way, new Soviet idols became the peasants from the series “24 hours at the Filippov’s” and the workers of “The Giant and the Builder”. The circulation of the magazine abroad could count on the help of foreign estimators of the Soviet model, who personally acted to spread these images, while in Russia the editor Pjatakov and valuable artists, such as A. Rodchenko, assured success and the quality of the content. So far research has focused on the graphic and artistic aspects of the magazine, mainly thanks to the studies of Erika Wolf, Professor of Art and Visual Culture at the University of Otago, while the historical, cultural and political importance of the magazine was marginally analyzed. It will be interesting to highlight language choices and editorial strategies used for such an issue, which should offer the internal élite a window on a changing country, while it should be a real shop window for estimators, foreign investors, simple spectators and also those who oppose the realization of the Soviet utopia in USSR.